2007
DOI: 10.1073/pnas.0704966104
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial protein therapy of angiogenic and arteriogenic factors remarkably improves collaterogenesis and cardiac function in pigs

Abstract: Establishment of functional and stable collaterals in the ischemic myocardium is crucial to restoring cardiac function after myocardial infarction. Here, we show that only dual delivery of a combination of angiogenic and arteriogenic factors to the ischemic myocardium could significantly reestablish stable collateral networks and improve myocardial perfusion and function. A combination of FGF-2 with PDGF-BB, two factors primarily targeting endothelial cells and vascular smooth muscle cells, remarkably promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 50 publications
(58 reference statements)
3
56
1
3
Order By: Relevance
“…Several studies have shown that PDGF-AB and PDGF-AA are indispensable for angiogenic events and are necessary for stabilizing newly formed blood vessels. [33][34][35] These chemokines may be important in the recruitment of other PACs or leukocytes, which in turn contribute to development and progression of angiogenesis 36 ; for example, MCP-1 can recruit PACs to a wound site to accelerate re-endothelialization. 37 Finally, although CMP-and GMP-derived PACs were able to elaborate higher levels of VEGF compared with MEP-or HSC-derived PACs, 10 we were surprised to find a striking absence of a decrease in the elaboration of VEGF in KLF10 Ϫ/Ϫ CMP-and GMP-derived PACs compared with WT PACs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that PDGF-AB and PDGF-AA are indispensable for angiogenic events and are necessary for stabilizing newly formed blood vessels. [33][34][35] These chemokines may be important in the recruitment of other PACs or leukocytes, which in turn contribute to development and progression of angiogenesis 36 ; for example, MCP-1 can recruit PACs to a wound site to accelerate re-endothelialization. 37 Finally, although CMP-and GMP-derived PACs were able to elaborate higher levels of VEGF compared with MEP-or HSC-derived PACs, 10 we were surprised to find a striking absence of a decrease in the elaboration of VEGF in KLF10 Ϫ/Ϫ CMP-and GMP-derived PACs compared with WT PACs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] In the light of our findings, we propose a model for the angiogenic switch based on the autocrine/paracrine FGF-2/FGFR1 activation by PGE 2 and FGF-2 synergistic interaction. FGFR1 acts as the master switch, because its activation by FGF-2 initiates an autocrine cycle of FGF-2 synthesis and FGFR1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…(Nillesen et al, 2007) In addition, some of the molecules involved in the angiogenesis stabilization signaling pathways (Table 1) have been delivered to the target tissue together with stimuli involved in the initiation step. PDGF-BB, a signaling protein stimulating MC proliferation and recruitment, has been used in combined delivery with VEGF Richardson et al, 2001) and FGF-2 (Cao et al, 2003;Lu et al, 2007). Tested in many animal models, the dual delivery of PDGF-BB, a vessel maturation factor, with VEGF or FGF-2 resulted in not only an increase in vessel quantity, but also improved vessel quality.…”
Section: Multiple Factors Deliverymentioning
confidence: 99%
“…Moreover, it allows long-term observation of vessel persistence. This method has only been used for evaluating growth factors or gene delivery, either as soluble factors (Cao et al, 2003;Lai et al, 2001;Lu et al, 2007) or immobilized in a hydrogel (Moon et al, 2010;Saik et al, 2010). Use of this model to evaluate cell therapies is still rare to our knowledge.…”
Section: In Vivo Modelsmentioning
confidence: 99%